Impacto de niveles de ansiedad y estrés en el aprendizaje virtual en estudiantes de medicina - Guevara Llanos, Bryan Anthony (2022)
To determine the levels of anxiety and stress in 119 students from fourth to sixth year of the Faculty of Medicine of the National University of Trujillo (UNT) at the beginning of exclusive e-learning measured with the SISCO Academic Stress Inventory and Self-assessed Anxiety Scale were applied at the beginning and the end of the semester; with a statistical test of marginal homogeneity to analyze changes in those levels of anxiety and stress between both measurements. It was evidenced that the impact of the ANXIETY levels was not significant in all the measures. Otherwise, the impact of medium-high and high STRESS levels showed that there was a significant change (p<0.001) between both measurements. It was a finding to show, for the students who use exclusive virtual learning, that not having their own electronic device and with a poor internet signal (p<0.001) in addition, having difficulty mastering virtual tools (p<0.05) are significantly correlated with the anxiety. Therefore, this research fulfills the objective of providing knowledge about the non-significant impact of anxiety levels, unlike stress levels, which were significant at medium-high and high levels in exclusive virtual learning in medical students, in addition to determining by finding the significant reasons for the use of the tools.